Internet Survey of Participant Demographics and Risk Factors for Injury in Competitive Agility Dogs - Evanow, Jennifer A.; VanDeventer, Gretchen; Dinallo, Gina; Mann, Sabine; Frye, Christopher W.; Wakshlag, Joseph J (VCOT Open, 2021)
Objective The aim of this study was to identify risk factors for an agility dog becoming injured during its career. We hypothesized that certain factors involved with the training, competition, age, sex, age of neuter, body condition, and management could be associated with the risk for injury.Study Design The outcome of interest in this cross-sectional survey design was injury versus no injury, and an initial univariable analysis screening was performed. All variables with a p-value of less than 0.20 in univariable analysis were entered into a multivariable logistic regression model. Manual backward stepwise removal was performed until remaining variables had a p-value of less than 0.05.Results Five-hundred responses were included in the analysis. In the final multivariable model adjusting for all other variables, breed, age, age at neuter, and level of competition remained associated with injury in the study population.Conclusion These findings support existing literature on the predispositions for injury with certain breeds and competition level. Our study further suggests, however, that there is a need to better understand how health decisions earlier in life may affect the prevalence for injury in the agility competitor, particularly regarding age at neutering and age of the competitor.
Keywords: canine; agility; injury; risk factors